USE AND PROTECTION OF LAND RESOURCES - Karshiev Shoymardon Elamonovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides detailed information on the efficient use of land resources, including their protection. as well as detailed information on the protection of soil resources, which is relevant today.